(untitled) - Takoorparsadh, Mohini

Bifacial photovoltaic module performance evaluation with reference to the solar spectrum and broadband irradiance (Stellenbosch : Stellenbosch University, 2023)
Thesis (MEng)--Stellenbosch University, 2023.